The Social Ideas ofAntanas Kaupas - Pruskus, Valdas (Problemos, 1997)
The activities and views of Antanas Kaupas (1870-1913), the Lithuanian Catholic sociologist, are analysed in the article. This Catholic intellectual little known to us, residing in the U.S.A., sent his articles and studies to the Lithuanian press in which he tried to ground the idea that the creation of an improved society must be based on common human values and must not contradict natural human rights. On the grounds of works of the U .S.A. psychological direction – sociologists’ ideas, such as A. Ross’, F. Giddings’, L. Ward’s, and A. Kaupas’ – the harmfulness of the total transformation of society under compulsion, ignoring human nature and human rights as well as an absence of social perspectives of it was proved. They mentioned that this transformation was propagated by social radicals. Defending the idea of the evolutionary development of the society, A. Kaupas kept to the view that total welfare may only be reached through a close collaboration of various social groups in which all members of society could be assured of equal rights and possibilities to disclose their abilities and initiative. The main aim of the nation is the restoration and consolidation of Lithuanian independence. For this realization, a concordance of all the layers of society as well as all the political parties is necessary. This can be ensured with tolerance and harmony.